Fanconi Anaemia associated with café au lait spots: a rare case report - Qazi, Maida; Khan, Bilal Ahmed; Kumar, Vijay; Mahnoor Amin; Kanza Ateeque (Journal of the Pakistan Medical Association, 2024)
Fanconi Anaemia is an autosomal recessive disorder, which is characterised by progressive pancytopenia, café au lait spots (>50%), bruising, petechie, recurrent infections, short height (50%), and thumb and radial bone anomalies (40%). Herein, is presented a case of a lean emaciated female child, who presented with the chief complaints of fever, loose stools and decreased appetite for one month was reported at Sindh Government General Hospital, Karachi, on February, 1, 2023. She had cutaneous findings of hyperpigmentation and café au lait spots and a tri-phalangeal thumb. On investigation, pancytopenia and a low reticulocyte count of 0.7% was also observed. Karyotype and chromosomal breakage test induced by Diepoxybutane confirmed her as a case of Fanconi Anaemia. Keywords: Fanconi Anaemia, Complete Blood Count, Diepoxybutane, Frontal-Occipital Circumference, National Institute of Blood Disease and Bone Marrow Transplantation.